Recapitulating the issues concerning the application of the bills of quantities - Bandi, Shamsul Hadi; Abdullah, Fadhlin; Amiruddin, Roslan (Faculti Alam Bina, UTM, Malaysia, 2014)
A preliminary review of the literature had indicated a growing concern over various issues concerning the application of the Bills of Quantities (BQ). Though eminent, these issues, however, have sparsely been highlighted on a fragmentary basis, thus requires a systematic restructuring to manifest its underlying meaning. Following this review, a study has been conducted with an aim to recapitulate and subsequently suggest some of the most compelling issues concerning the application of the BQ. In this regard, it has objectively strived to identify relevant issues from the literature and ensue by critically synthesizing the outcome in response to the aim. Correspondingly, with support from tables and models developed to represent the concepts, the study has proposed three main categories of issues from the restructuring process. These are: (1) issues related to information, (2) issues related to format and (3) issues related to the method of working. Issues related to information have been suggested from the process as the issue considered most compelling thus warranting further consideration by the industry. The significance of this study is on the methodological way of restructuring and refocusing the issues related to the BQ. The finding has the potential prospect for future research and act as a basis from which the industry’s awareness can be bolstered.